Fine System Of Ringgit In Simbur Cahaya Manuscript: Analysis Using Artificial Intelligence - Hudaidah; Susanti, L.R. Retno; Vianty, Machdalena; Darme, Made (PURBAWIDYA, 2025)
Simbur Cahaya manuscript is a customary law originating from the government of Palembang Lamo, precisely in the 17th century, and was applied in the interior regions of Palembang. During the Dutch colonial period, the Dutch Assistant Resident Van den Bossche successfully completed the codification of the Simbur Cahaya law in 1854. This law was subsequently revised multiple times, including in the years 1862, 1873, 1875, 1876, 1890, 1894, 1897, 1913, 1922, 1927, and 1939. An analysis using artificial intelligence (AI) has revealed a unique feature of this manuscript: all legal violations in society were sanctioned with fines in the form of ringgit. This paper aims to explore how ringgit was used as a fine to punish members of society who violated the rules. The focus of this study is to trace how ringgit was applied as a sanction for legal offenders. The research employs historical research methods, including heuristics, source criticism, interpretation, and historiography, with the primary source being the Simbur Cahaya manuscript codified by the Dutch in 1922 and 1927. The novelty of this study lies in the use of artificial intelligence to interpret the Simbur Cahaya manuscript as the primary source of research. Based on the analysis, it was found that all social punishments recorded in the Simbur Cahaya manuscript for individuals who violated the rules were always accompanied by fines in the form of ringgit, ranging from a minimum of half a ringgit to a maximum of six ringgit.